Parola del corpo e corpo della parola. Espressione, percezione, linguaggio tra Benjamin e Merleau-Ponty - Gurisatti, Giovanni (Scenari, 2024)
A convergence between Benjamin’s and Merleau-Ponty’s philosophy of language is given by the two authors’ critique of the instrumental and functionalist (semiotic) conception of language, which neglects its ‘physiognomic’, mimetic, gestural and expressive aspects. Drawing on a common frame of reference, Benjamin and Merleau-Ponty investigate both the “word of the body”, i.e. the origin of language from synaesthetic and multisensory corporeity, and “the body of the word”, i.e. the capacity that the linguistic signifier has to be, at the same time, the communicative instrument of an abstract meaning, and the expressive medium of a concrete meaning, which offers itself to perception. For both, such a non-instrumental conception of language – typically hermeneutic – finds its highest expression in both poetic-literary writing and the particular style of exposition that is characteristic of authentic philosophical meditation.